(untitled) (Research in Agriculture Livestock and Fisheries, 2018)
Garole sheep is very popular for its biannual lambing and disease resistance characters. To evaluate some selected serum electrolytes (Na, K and P) ions in apparently healthy Garole sheep at Sundarban region under Shyamnagar Upazila of Satkhira district, blood samples were collected from 20 Garole sheep (8 males and 12 females) of aged about 6-48 months containing male lambs, rams, female lambs, pregnant ewes and lactating ewes according to the age, sex and physiologic status. Serum was separated and used for biochemical analysis for the measurement of target serum electrolytes. The results of the range and mean ± standard error (SE) of serum electrolytes are as follows: sodium 280-400 ppm and 342.96±7.19 ppm, potassium 30-55 ppm and 34.37 ± 0.72 ppm and phosphorus 40-90 ppm and 70.98 ±1.76 ppm respectively. The significant differences (P<0.05) between males and females in serum ions levels was recorded. It can be concluded that Na, K and P ion level in serum was higher in male than female and significant differences in ion level varies according to physiologic status of female Garole sheep. Res. Agric., Livest. Fish.5(3): 351-358, December 2018